2016
DOI: 10.1104/pp.15.01736
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Triggered Electrophysiological Reactions: Candidates for Systemic Signals in Higher Plants and the Challenge of Their Identification

Abstract: In stressed plants, electrophysiological reactions (elRs) are presumed to contribute to long-distance intercellular communication between distant plant parts. Because of the focus on abiotic stress-induced elRs in recent decades, biotic stress-triggered elRs have been widely ignored. It is likely that the challenge to identify the particular elR types (action potential [AP], variation potential, and system potential [SP]) was responsible for this course of action. Thus, this survey focused on insect larva feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 69 publications
(113 reference statements)
5
92
0
Order By: Relevance
“…Numerous modern investigations (e.g., Favre & Agosti, ; Fromm & Lautner, ; Pickard, ; van Bel et al, ; Volkov & Ranatunga, ; Yan et al, ; Zimmermann, Mithöfer, Will, Felle, & Furch, ; and references therein) have confirmed the validity of some of these early claims of electrical communication by Bose. Because the phloem is to be found throughout any higher plant, the potential for very long distance communication in large plants exists, incidentally, at considerable speeds (Fromm & Bauer, ; Fromm & Lautner, ; Galle, Lautner, Flexas, & Fromm, ; Yan et al, ; Zimmermann et al, ). Action potentials in plants can move from 0.5 to 40 cm/sec, and the distance covered may be helped by the recently described system potentials (Choi, Hilleary, Swanson, Kim, & Gilroy, ; Zimmermann et al, ).…”
Section: The “Nervous” System In Plantsmentioning
confidence: 86%
“…Numerous modern investigations (e.g., Favre & Agosti, ; Fromm & Lautner, ; Pickard, ; van Bel et al, ; Volkov & Ranatunga, ; Yan et al, ; Zimmermann, Mithöfer, Will, Felle, & Furch, ; and references therein) have confirmed the validity of some of these early claims of electrical communication by Bose. Because the phloem is to be found throughout any higher plant, the potential for very long distance communication in large plants exists, incidentally, at considerable speeds (Fromm & Bauer, ; Fromm & Lautner, ; Galle, Lautner, Flexas, & Fromm, ; Yan et al, ; Zimmermann et al, ). Action potentials in plants can move from 0.5 to 40 cm/sec, and the distance covered may be helped by the recently described system potentials (Choi, Hilleary, Swanson, Kim, & Gilroy, ; Zimmermann et al, ).…”
Section: The “Nervous” System In Plantsmentioning
confidence: 86%
“…d). Such restricted propagation of typical APs, in contrast to VPs, was also recently documented in noncarnivorous plants (Zimmermann et al ., ) and is also known in sensitive plant ( Mimosa pudica ; Fromm & Lautner, ). But Escalante‐Pérez et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that VPs are induced by hydraulic waves in the xylem that affect mechanosensitive ion channels (Mancuso, ) or, if a chemical is transported, via ligand‐activated channels (Malone, ). The SPs were recognized only recently as signals with reverse polarity with all‐or‐nothing character and are not caused by a hydraulic pressure surge (Zimmermann et al ., , ).…”
Section: Introductionmentioning
confidence: 99%